The effect of a four-week strength and power program on sprint performance in court-based wheelchair athletes - Dineen, A.; Warne, J. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: It is well documented that strength and power training has positive effects on sprinting performances in able-bodied athletes, but there is a lack of evidence investigating if the same could be said for wheelchair athletes. Therefore, the purpose of this study was to investigate if a four-week strength, power and resisted sprint training program improved maximal strength, power and sprint speed performance in male court-based wheelchair athletes, post a COVID-19 detraining period.